INVESTIGATION OF THE MORPHOFUNCTIONAL CONDITION OF THE WHITE SILVER CARP (HYPOPHTHALMICHTHYS MOLITRIX) FROM THE ILE RIVER AND KAPSHAGAI RESERVOIR (Eurasian Journal of Ecology, 2024)
In recent decades, the ecosystems of the Ile River and the Kapshagai reservoir have been subject to anthropogenic pressure, which reduces the productivity of these reservoirs and causes the death and disappearance of native and introduced fish species of commercial importance. In this work, the morphofunctional state of silver carp (Hypophthalmichthys molitrix) from different parts of the Ile River and the Kapshagai reservoir, as well as one of the pond farms in the Almaty region, where it is grown, was studied. Chemical analysis of the surface waters of the studied sections of the Ile River and the Kapshagai Reservoir revealed the presence of 9 heavy metals, 3 of which: Pb, Zn, Cu showed an excess of the MPC for fishery reservoirs (MPC). The content of these heavy metals in the surface waters of the pond farm was below the MPC, therefore the water quality in it was accepted as conditionally clean (control). Histological examination of samples of organs (gills, liver, intestines) of silver carp revealed significant destructive changes in individuals caught at 4 different points in the upper reaches of the Ile River and the Kapshagai reservoir (near the dam and the city of Konaev), and to a lesser extent in fish from the northern part of Kapshagay. It was also revealed that the condition of the fish from the pond farm was within normal limits. The morphometric analysis of the most important bioindicative indicators of fish organs quantitatively confirmed histological observations. Based on the results obtained and data from other authors, a conclusion is made about the probable bioaccumulation of HMs from contaminated water in the body of fish, which leads to disruption of biochemical and physiological homeostasis, and ultimately affects the structural organization of organs and the survival of aquatic organisms.Key words: Ile River, Kapshagai Reservoir, heavy metals, silver carp, histology, morphometry